Model Ontologi untuk Penjadwalan Kuliah di Program Studi Teknik Informatika Fakultas Teknik Universitas Muria Kudus - Nurkamid, Mukhamad; Jazuli, Ahmad; Nugroho, Dimas Adi; Mahfud, Rizal Abdullah (Jurnal Transformatika, 2021)
The purpose of this study is to build a data model for scheduling lectures at the Informatics Engineering Study Program, Faculty of Engineering, Muria Kudus University uses ontology as part of the implementation of semantic web technology. System built based on existing schedule data in the Informatics Engineering Study Program, such as data days, courses, credits, space and time stored in RDF / OWL format. The use of a lot of data with different storage formats becomes problems in finding valid information. To overcome this, it is necessary a system that can provide complete information is needed, namely with using semantic web technology. The semantic web is used to understand meaning of a word and concept, because it builds interconnected resources. Semantic web implementation is built using the ontology approach applied to RDF/OWL format. The results of this study are improving the ability of computers to search for more informationrich lecture schedules in the Informatics Engineering Study Program.